L-Arginine Reduces Nitro-Oxidative Stress in Cultured Cells with Mitochondrial Deficiency - Camila D. S. Barros (Nutrients, 2021)
L-Arginine (L-ARG) supplementation has been suggested as a therapeutic option in several diseases, including Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like syndrome (MELAS), arguably the most common mitochondrial disease. It is suggested that L-ARG, a nitric oxide (NO) precursor, can restore NO levels in blood vessels, improving cerebral blood flow. However, NO also participates in mitochondrial processes, such as mitochondrial biogenesis, the regulation of the respiratory chain, and oxidative stress. This study investigated the effects of L-ARG on mitochondrial function, nitric oxide synthesis, and nitro-oxidative stress in cell lines harboring the MELAS mitochondrial DNA (mtDNA) mutation (m.3243A>G). We evaluated mitochondrial enzyme activity, mitochondrial mass, NO concentration, and nitro-oxidative stress. Our results showed that m.3243A>G cells had increased NO levels and protein nitration at basal conditions. Treatment with L-ARG did not affect the mitochondrial function and mass but reduced the intracellular NO concentration and nitrated proteins in m.3243A>G cells. The same treatment led to opposite effects in control cells. In conclusion, we showed that the main effect of L-ARG was on protein nitration. Lowering protein nitration is probably involved in the mechanism related to L-ARG supplementation benefits in MELAS patients.